2022
DOI: 10.1007/s00221-022-06488-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vestibular stimulation on gait stability when walking at different step widths

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The models proposed by Wang & Srinivasan Special issue: Effects of aging on locomotor patterns from several other studies on mediolateral control 15,16,17,18,19,20,21,22,23 and to data from one other study on anteroposterior control 13,24 . Jin et al 24 showed that, as for mediolateral foot placement, the anteroposterior center of mass position and velocity in the corresponding direction only provide a good prediction of anteroposterior foot placement, supporting a more parsimonious model for the control of foot placement than the original model 13 .…”
Section: Foot Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…The models proposed by Wang & Srinivasan Special issue: Effects of aging on locomotor patterns from several other studies on mediolateral control 15,16,17,18,19,20,21,22,23 and to data from one other study on anteroposterior control 13,24 . Jin et al 24 showed that, as for mediolateral foot placement, the anteroposterior center of mass position and velocity in the corresponding direction only provide a good prediction of anteroposterior foot placement, supporting a more parsimonious model for the control of foot placement than the original model 13 .…”
Section: Foot Placementmentioning
confidence: 99%
“…For steady-state walking, the correlation between center of mass state and foot placement 13 described in section 2.1 has been interpreted as reflective of active control, but it could also result from passive coupling of movements of the leg to the movements of the upper body 60 . For mediolateral foot placement, it has been shown that lowering stabilization demands, by increasing prescribed step width, decreases the strength of the coupling between mediolateral center of mass state and foot placement 15,23 . This phenomenon is even clearer when subjects walking on a treadmill are externally stabilized by a springloaded construction, creating a force-field that corrects mediolateral deviations of the center of mass 19 .…”
Section: Sensing and Actuation Of Foot Placementmentioning
confidence: 99%
“…1 B & 1 C ). These signal characteristics were identical to those used previously (Magnani et al., 2021; Magnani et al., 2023), in which measurable responses to EVS in muscle activity, ground reaction force and foot placement were reported, demonstrating the effectiveness of this EVS protocol.…”
Section: Methodsmentioning
confidence: 99%
“…A narrow step width, which reduces the base of support, poses greater challenges to stability and, as such, increases the demands on postural control (Arvin et al., 2016; Magnani et al., 2023). A previous study demonstrated that vestibular contributions are modulated by the stabilization demands of walking (Magnani et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In aging and age-related diseases, errors in foot placement, changes in pelvis velocity and movement, limited active control of ankle movements, or even the typical changes in steps metrics (width, length) may reflect in the reduced stabilization of walking. For instance, by increasing step width, typically observed in older and PD individuals, the strength of the coupling of the mediolateral CoM state and foot placement may decrease 24 . Additionally, as also mentioned by van Leeuwen et al 23 , sensing and actuation of those mechanisms are strictly relevant to actively controlling stability during gait.…”
Section: Mechanism To Control Stability During Walkingmentioning
confidence: 99%